PENGEMBANGAN MODUL AJAR MATERI GEOMETRI UNTUK MENUMBUHKAN SPATIAL SKILLS SISWA SEKOLAH DASAR - Wardhani, Indah Setyo (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
A spatial imaginative learning model to develop elementary school students' spatial skills has been developed by researchers, but its implementation requires a teaching module. This research aims to describe the process and results of developing teaching modules that have valid criteria for developing the spatial skills of elementary school students. The type of research chosen is development research. The development theory chosen is Plomp theory with stages: 1) initial investigation, 2) prototype development, and 3) assessment. The results of the research are teaching module products that have valid criteria and have been assessed by experts through reliable teaching module validation sheets. Implementation of research shows that teaching modules can be used as supports for spatial imaginative learning models and can be applied in geometry learning.